(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Landforms are typical landforms of the Earth’s surface that are formed by natural processes of erosion, denaturation and deposition (Strehler and Strahler, 1996). Landforms are the result of geologic and geomorphological processes that occur continuously on the Earth’s surface. If the relief of the surface is observed, then it appears that the relief and topography of the surface are stable and unchanging. But if observed closely, the variability of these reliefs and landforms of the surface is clearly visible over time. Because "change is the law of nature". The forces acting in the interior of the earth are called endogenous forces. By these active internal forces, the relief of unevenness is initiated on the surface and different types of landforms are formed and developed. These internal forces and different types of movements, especially affect the emergence and development of landforms by means of terrestrial forms (such as cracks, fractures) etc. In this way, if When the endogenous forces create inequalities and inequalities on the surface, then exogenous forces constantly try to destroy these inequalities on the surface. Thus exogenous forces are plane stabilizing forces. If this happens, then the exogenous forces have to make efforts for a long time to remove these disparities.The main function of the exogenous forces is Denudation.